Chlorophyll regulates accumulation of the plastid-encoded chlorophyll proteins P700 and D1 by increasing apoprotein stability. - Kim, J (1994)
Chlorophyll protein accumulation in barley (Hordeum vulgare L.) chloroplasts is controlled posttranscriptionally by light-induced formation of chlorophyll a. The abundance of translation initiation complexes associated with psbA, psaA, and rbcL mRNAs was measured using extension and inhibition analysis in plants grown in the dark for 4.5 d and then illuminated for up to 16 h. Light-induced accumulation of the chlorophyll proteins was not accompanied by changes in the abundance of translation initiation complexes, indicating that regulation of chlorophyll protein accumulation at this stage of development does not occur at the level of translation initiation. Translational runoff assays were performed in the presence of lincomycin, an inhibitor of translation initiation, to determine whether chlorophyll protein accumulation was regulated at the level of translation elongation. The extent of ribosome runoff of psaA and psbA mRNAs was similar in the presence or absence of chlorophyll, indicating that chlorophyll did not alter chlorophyll protein translation elongation. Polysome-associated D1 translation intermediates were radiolabeled in the presence or absence of chlorophyll, even though full-length D1 accumulated only in the presence of chlorophyll. Chlorophyll influenced the stability of D1 translation intermediates to a small extent and greatly increased D1 stability after release from ribosomes. Overall, these results demonstrate that light-induced chlorophyll biosynthesis triggers the accumulation of the chlorophyll proteins D1 and P700 in barley chloroplasts by enhancement of chlorophyll apoprotein stability.